Hon Julia Gillard - 27th Prime Minister of Australia. - Gillard, Julia ([Victoria] : Julia Gillard, 2013)
Julia Gillard was sworn in as the 27th Prime Minister of Australia on 24 June 2010 and served in that office until June 2013... ...Ms Gillard is the first woman to ever serve as Australia's Prime Minister or Deputy Prime Minister. In October 2012, Ms Gillard received worldwide attention for her speech in Parliament on the treatment of women in professional and public life...
Title from title screen (viewed on 28 April 2016)
Mode of access: Available online. Address as at 05/05/2016
Selected for archiving
Keywords: Gillard, Julia; Prime ministers -- Australia; Australian